An Analysis Of Derivational And Inflectional Morphemes In The Lyrics Of Calum Scott’s Songs In The Album “Bridges” - Exlesia Pestaria Lumban Toruan (EDUJ : English Education Journal, 2023)
Morphology studies the intricate forms of words and the influence of changes in word forms on word categories and meanings. Morphemes, as the smallest grammatical units with meaning, are the primary focus of morphology. Morphemes cannot be further divided into smaller linguistic units. This research aims to investigate derivational and inflectional morphemes in the lyrics of Calum Scott’s songs in the album “Bridges”. The qualitative method is employed in this study, which reveals the presence of derivational and inflectional morphemes in the lyrics. The analysis demonstrates the existence of various types of derivational and inflectional affixes. Inflectional morphemes, particularly affixes, are found to be more dominant in the lyrics of Calum Scott’s songs in the album “Bridges”. The findings of this research identify 50 derivational and 99 inflectional morphemes. In derivations, 21 types of affixes are discovered, including prefixes such as re-, pre-, a-, sur- and suffixes such as -ent, -le, -ion, -ful, - less, -ing, -ly, -ain, -ed, -ness, -ment, -y, -ry, -er, -ty, -st, and -ical. Furthermore, there are 8 types of inflectional morphemes, namely plural, past tense, past perfect, comparative, possessive, third-person singular, gerund, and progressive.